New Horizons in the Law of the Sea - Leary, David; Chakraborty, Anshuman (Victoria University of Wellington Law Review, 2005)
This article summarises the proceedings of the symposium held at Victoria University of Wellington in September 2004 to mark the tenth anniversary of the United Nations Convention on the Law of the Sea. The authors highlight the key themes of the symposium, basing their discussion on the five topics of maritime security, enforcement and compliance in fisheries law, Pacific regional issues, dispute resolution and the law of the sea, and future directions for the law of the sea.